Candra Dewi All Hubungan Minat Baca Terhadap Kemampuan Menulis Narasi Pada Peserta Didik Di Sekolah Dasar - Moch. Khabibur Rizal; Elyana Rosyita; Farida Maulida; Candra Dewi; Sekar Dwi Ardiantis; Erik Aditia Ismaya (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
The aim of this research is to identify the relationship between interest in reading and the ability to understand discourse and writing skills in class III and IV students at SD Negeri 2 Karangbener, with a total of 24 students. The data analysis technique used is the correlation test. The research results show that there is a relationship between interest in reading and the ability to write narratives in students. This can be seen from the results of the bivariate test which was obtained with a calculated r value of 0.074 and a p-value of 0.05, so H0 can be accepted, showing that there is an influence between interest in reading and narrative writing skills.